3D Simulator with hardware-in-the-loop capability for the micromouse competition - Piardi, Luis (2019)
Robotics competitions are a way to challenge researchers, roboticists and enthusiastic to address robot applications. One of the well-known international competition is the Micromouse where the fastest mobile robot to solve a maze is the winner. There are several topics addressed in this competition such as robot prototyping, control, electronics, path planning, optimization, among others while keeping the size of the robot as small as possible. A simulation can be used to speed-up the development and testing algorithms but faces the gap between a simulation and reality, specially in the dynamics behaviour. There are some simulation environments that allow to simulate the Micromouse competition, but in this paper, an Hardware-in-the-loop simulator tool is presented where the simulated robot is controlled by the same microcontroller used by the robot. By this way, the developed algorithms are tested and validated with the limitations and constraints presented in the real hardware, such as memory and processing capabilities. The robot dynamics, the slippage of the wheels, the friction and the 3D visualization are present in the simulator. The presented results show that the same code and hardware controlling the simulated and the real robot identically.